Development of microsatellite markers in sweet passion fruit, and identification of length and conformation polymorphisms within repeat sequences. Issue 6 (26th July 2013) - Penha, Helen Alves; Pereira, Guilherme Da Silva; Zucchi, Maria Imaculada; Diniz, Augusto Lima; Vieira, Maria Lucia Carneiro; Flachowsky, H.
Abstract The aim of this study was to construct and characterize an SSR‐enriched genomic library for Passiflora alata, a fruit species native to the Brazilian plateau and the eastern Amazon region. There is potential to improve this crop, as the fruit is attractive because of its pleasant aroma and flavour characteristics. Of 862 sequences, 391 (45%) were found to have SSRs. We identified 412 microsatellites: 69% were classified as perfect, 23% imperfect, 5% interrupted and 3% were compound microsatellites. The main types of repeat sequences were dinucleotide (62.5%) and trinucleotide (23%) repeats. It was possible to design 312 primer pairs, and 229 of them were synthesized and tested. The amplicons were electrophoresed using denaturing and non‐denaturing gels to screen for divergence between two phenotypically distinct parents of a mapping population of P. alata. Length and conformation polymorphisms within repeat sequences amounted to 35% and 28%, respectively. The importance of the development of SSR markers for sweet passion fruit and the effectiveness of the SSCP approach to increase the available number of polymorphic SSRs are discussed.